External shocks and labor market reforms in autocracies and democracies: Evidence from oil price windfalls - Markus Brückner; Gabriele Ciminelli; Norman Loayza (Asian Development Bank (ADB), 2024)
We examine the relationship between oil price windfalls and labor market regulation empirically through panel regressions in a sample of 83 countries spanning 1970-2014. We find that oil price windfall gains lead to a deregulation of the labor market in autocracies but have no effects in democracies. Windfall losses instead cause a sizeable deregulation in democracies but have limited effects in autocracies. We then consider possible transmission channels. Democracies appear to redistribute the rents stemming from a positive windfall by increasing government expenditure. Rent extraction and economic efficiency considerations are instead both plausible deregulation drivers following windfall gains in autocracies, as expenditures are not raised, while gross domestic product and employment gradually increase after positive windfalls. Finally, the deregulation following windfall losses in democracies is consistent with the crisis-inducedreform hypothesis, as windfall losses deteriorate the current account and budget balances and increase the probability of a systemic banking crisis.
Keywords: F16; J41; O13; P11; P16; Q02; 330; oil price; windfalls; labor market; deregulation; political institutions